Students’ Communication Skill and Algebraic Thinking through Commognitive Framework in Algebra Learning - Pratiwi, Weni Dwi; Putri, Ratu Ilma Indra; Hiltrimartin, Cecil; Zulkardi (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Mathematical communication is a skill to articulate mathematical ideas through written and verbal expressions. Despite its importance, students often exhibit difficulties in initiating and organizing mathematical ideas, particularly in written form. Prior research highlights the critical role of communication in fostering early algebraic thinking. This study aims to: (1) examine students’ mathematical communication skills and explore how it reflects early algebraic thinking, using the commognitive framework, which encompasses word use, visual mediators, narratives, and routines, and (2) describe statistically the relationship between algebraic thinking and oral communication skills. A descriptive research design with mixed-methods approach was employed, involving 29 eighth-grade students as participants. Data was collected through written tests, and the results were analyzed descriptively. The findings indicate that four students demonstrated excellent communication skills, nine students were categorized as good, 11 students as fair, three students as poor, and two students as very poor. Further analysis showed that students with stronger communication skills more effectively conveyed algebraic ideas. The results also underscore the commognitive framework practical application in enhancing students’ conceptual understanding. This study contributes to a deeper understanding of how students communicate, reason algebraically, and demonstrates the potential of the commognitive framework to support instructional design and skill development in mathematics education.